Direct Plasma Deposition of Lysozyme‐Embedded Bio‐Composite Thin Films. Issue 11 (9th June 2015) - Palumbo, Fabio; Camporeale, Giuseppe; Yang, Yi‐Wei; Wu, Jong‐Shinn; Sardella, Eloisa; Dilecce, Giorgio; Calvano, Cosima Damiana; Quintieri, Laura; Caputo, Leonardo; Baruzzi, Federico; Favia, Pietro
Abstract : Bio‐composite coatings, consisting of an organic matrix embedding a bioactive molecule, have been deposited by means of atomizer‐assisted atmospheric pressure plasma. Ethylene was chosen as the precursor of the matrix, while the atomizer was fed with a water solution of lysozyme. Coatings chemical composition was investigated by XPS, FTIR and MALDI‐TOF spectroscopies, and it has been proved that the one‐step inclusion of protein domains in the composite coatings is successful and lysozyme chemical structure is only slightly altered. The amount of embedded lysozyme is as high as 14 μg/cm 2 as evaluated from water release test. Finally, the activity of the plasma‐embedded protein is close to that of pure lysozyme as verified against Micrococcus lysodeikticus ATCC 4698 through an agar plate diffusion test. Abstract : Aerosol‐assisted atmospheric pressure plasma has been properly optimized to prepare lysozyme‐containing composite coatings. The antibacterial enzyme, entrapped with a density as high as 14 µg/cm 2, is released in water keeping its bio‐activity. The set of characterization techniques, primarily MALDI‐MS and HPLC, confirms that lysozyme mostly retains the structure.